Efficient, Compassionate, and Fractured: Contemporary Care in the ICU - Bishop, Jeffrey P. (The Hastings Center report, 2014)
Alasdair MacIntyre described the late modern West as driven by two moral values: efficiency and effectiveness. Regardless of whether you accept MacIntyre's overarching story, it seems clear that efficiency and effectiveness have achieved a zenith in institutional health care structures, such that these two aspects of care become the final arbiters of what counts as “good” care. At the very least, they are dominant in many clinical contexts and act as the interpretative lens for the judgments of successful health care managers. The drive of efficiency can also be seen in “lean” management methods (originally imported from the automotive manufacturing industry) increasingly deployed in the intensive care unit. This drive gives us pause. The high stress of the ICU is exacerbated by the enormous complexity of technological interventions designed to maintain physiological functioning as the body heals, as well as the ever-present concerns related to cost, effectiveness, and efficiency. The ICU, therefore, provides an illustrative view of the challenges facing clinicians, as well as resource managers, in terms of delivering care. In short, the goal of technocratic efficiency often ends up at odds with humane purposes. To better understand these contemporary health care dynamics, we conducted a limited series of focus group discussions and interviews with residents experienced in the challenges of delivering care in the ICU environment. In what follows, we highlight some narrative observations drawn from these focus groups. We found a recurrent and disconcerting refrain among our informants that has not been adequately described or addressed in the literature: technocratic management techniques have crept into and bifurcated clinical care strategies in the ICU. Specifically, we highlight the influence of concerns around efficiency and effectiveness and the ways in which these foci have contributed to a bifurcation in care in the ICU along two trajectories: either compassionate care or curative care.